The #IVF journey: content analysis of IVF videos on TikTok - Peipert, Benjamin J.; Wu, Jenny; Taylor-Cho, Ian A.; Lunn, Siera R.; Swartz, Jonas J.; Acharya, Kelly (Reproductive biomedicine online, 2023)
What patient populations and outcomes are depicted on IVF videos on the short-form video-sharing application ‘TikTok’? This cross-sectional study investigated the 100 most-viewed videos utilizing the #IVF hashtag on TikTok. Only videos in English or Spanish were included in the analysis. An automated web-scraping platform was used to extract information from these videos. Standardized video coding was used to evaluate the featured subject(s), phase of care and IVF outcomes from the videos. Videos meeting the inclusion criteria (n=93) had 731 million views, 91 million likes and 893,000 shares. Patients’ personal stories about IVF are over-represented relative to videos created by healthcare professionals. #IVF videos popular on TikTok disproportionately depict same-sex couples (38.1%), gestational carriers (14.0%), multiple gestations (60.0%) and live births (89.3%) relative to real-world data. Among the videos making scientific claims (n=16), nearly all were moderately to highly accurate (93.8%). Most videos had a positive (55.9%) or neutral (5.5%) tone towards IVF. Popular #IVF videos on TikTok contribute to public discourse about infertility, and highlight demographics that have traditionally been under-represented in health care. Videos rarely focused on health education or made informational claims, with low scores on measures of quality of information and actionability. This gap represents an opportunity for health providers and educators to create more engaging and educational content to reach patients considering IVF.